Effectiveness of In-Service Pre-Primary Teacher Training Package on School Readiness of Children - Chandra, Reetu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Indian pre-primary education system is vast and diverse. Thus, ensuring that teachers are equally competent is a challenge. The situation adversely affects the readiness of pre-primary children for formal schooling leading to low retention and high dropout rates in early primary grades. An experiment was conducted in eight pre-primary classes of Municipal Corporation of Delhi schools, eight teachers, and 176 children with the objectives to identify the gaps in the performance of teachers, to identify gaps in the level of school readiness of children and to develop an in-service pre-primary teacher training package on the school readiness of children and record its effectiveness on the performance of teachers and the level of school readiness of children. The data was collected using ‘Checklist for Teacher Performance’, ‘School Readiness Instrument’ and ‘Rating Scale’. The experiment employed ‘Pre-test Post-test Control Group Experimental Design’. Gaps in the performance of teachers and the level of school readiness of children were identified through a pre-test. To address gaps, a package was developed and six days of training to the experimental group teachers were given. Post-test results revealed that after training there was a 29.75% improvement in the performance of teachers. In the case of experimental group children, a gap of 38.8% in their level of school readiness on pre-test reduced to 8.8% on post-test. Comparison of mean difference from pre-test to post-test of both the groups shows effect size 0.907 with a p-value of 0.000 level of significance. Correlation analysis suggests a significant correlation between the performance of teachers and the performance of children.